Radar cross section reduction and gain enhancement of slot antenna using polarization conversion metasurface for X‐band applications. Issue 10 (12th July 2021) - Chatterjee, Joysmita; Mohan, Akhilesh; Dixit, Vivek
Abstract: A compact metasurface loaded slot antenna with wide impedance and radar cross section (RCS) bandwidths and a high gain is reported in this communication. The proposed polarization conversion metasurface (PCMS) and its mirror image is arranged into four quadrants and placed atop the slot antenna. A 10‐dB monostatic RCS reduction from 7.85 to 12.25 GHz is achieved due to the 180° phase difference of the reflected waves from the PCMS and its mirror image. The gain of the proposed structure gets enhanced by almost 3 dB compared to the radiator alone, throughout the operating band, by partially removing the PCMS just above the slot radiator. The antenna is suitable for use in stealth applications in X‐band communication. The antenna structure is fabricated and measured and a good agreement is observed between the simulated and measured results.